Probability of events involving logical aspects - Fernandes, José António (2018)
In this article, we study the Probability's knowledge of prospective primary school teachers, when there are logical aspects involved in the formulation of events. Forty-six students participated in the study, from a University in Northern Portugal, who had to resolve a three-item task in the context of a formal evaluation: the first one, on the union probability (connective or), the second one, on the joint probability (connective and), and the third one, on the conditional probability, in which the conditioned event is, in turn, a joint probability (connective and). In terms of the main results of the study, it was found that the students showed a very limited performance, frequently changing the connectives and and or, the inclusive disjunction with the exclusive disjunction and in the disjunction considered as incompatible non-disjoint events.